2021
DOI: 10.1007/s00256-021-03730-x
|View full text |Cite
|
Sign up to set email alerts
|

Osseous defect of the anteroinferior femoral head: is it associated with femoroacetabular impingement (FAI)?

Abstract: Objective To evaluate the prevalence, morphology, and clinical significance of a repeatedly observed yet not examined circumscript osseous defect at the anteroinferior aspect of the femoral head, termed femoral head defect. Materials and methods Retrospective study with approval of the institutional review board. There was informed consent by all individuals. Magnetic resonance imaging (MRI) hip examinations of 970 individuals (age 15 to 55) were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…1 Another study reported cysts and femoral head defects on the anterior-inferior femoral head and found an association with reduced FV. 4 A previous study evaluated hips with femoral retroversion and bipolar hemiarthroplasty and found an osseous impingement conflict in flexion in all hips. 47 The authors reported extra-articular subspine impingement in 51 of 60 hips (85%).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…1 Another study reported cysts and femoral head defects on the anterior-inferior femoral head and found an association with reduced FV. 4 A previous study evaluated hips with femoral retroversion and bipolar hemiarthroplasty and found an osseous impingement conflict in flexion in all hips. 47 The authors reported extra-articular subspine impingement in 51 of 60 hips (85%).…”
Section: Discussionmentioning
confidence: 97%
“…1 Another study reported cysts and femoral head defects on the anterior-inferior femoral head and found an association with reduced FV. 4…”
Section: Discussionmentioning
confidence: 99%
“…8 This defect is suggested as a variant of the herniation pit; however, an association with repeated impaction in individuals with reduced femoral antetorsion has also been proposed. 8,9 Herniation pits are thought to result from mechanical forces originating from the anterior joint capsule and overlying muscles, causing herniation of soft tissue and synovium through a defect or perforation in the bony cortex. An association with FAI was suggested as a possible causative factor of these lesions 10 ; however, this association is widely disputed.…”
Section: Herniation Pitmentioning
confidence: 99%
“…4 ). 8 This defect is suggested as a variant of the herniation pit; however, an association with repeated impaction in individuals with reduced femoral antetorsion has also been proposed. 8 9…”
Section: Imagingmentioning
confidence: 99%